Correlation of moisture content to selected mechanical properties of rice grain sample - Renny Eka Putri; Yahya, Azmi; Adam, Nor Maria; Abd Aziz, Samsuzana (Indonesian Society for Knowledge and Human Development, 2015)
The correlation between different levels of moisture content on rupture force at different grain orientation was determined for rice grain. Rupture forces of MR 220 CL2 variety rice grains under vertical and horizontal orientations were conducted in a compression test with an Instron 5500 Universal Testing Machine. It was found that the rupture force of rice at the horizontal orientation was higher than those at the vertical orientation for the entire range of moisture content. The correlation level of rice moisture content to rupture force of the grain were r = 0.933 and r = 0.924 for horizontal orientation and vertical orientation, respectively.